Toward a secure digital society: The influence of digital security awareness on students' personal data protection behavior - Lucia Apria; Darwis Robinson Manalu (Societa: Journal of Society and Change, 2026)
The growth of the digital society has increased technology use while simultaneously amplifying the risk of personal data breaches, yet the relationship between digital security awareness and personal data protection behavior among university students remains underexplored. This study aimed to examine the influence of digital security awareness on the personal data protection behavior of students at Universitas Methodist Indonesia. A quantitative causal-associative approach was employed involving 102 respondents selected through convenience sampling, with data collected using questionnaires and analyzed through simple linear regression. The findings revealed that digital security awareness had a positive and significant effect on personal data protection behavior (B = 0.621; t = 9.876; p < 0.001) and explained 49.4% of the behavioral variance (R² = 0.494). These findings highlight that strengthening digital security awareness is fundamental to fostering personal data protection behavior and provides empirical support for enhancing cybersecurity literacy initiatives within the digital society. Abstrak Perkembangan masyarakat digital meningkatkan intensitas penggunaan teknologi sekaligus memperbesar risiko kebocoran data pribadi. Namun, hubungan antara kesadaran keamanan digital dan perilaku perlindungan data pribadi mahasiswa masih belum banyak dikaji secara empiris. Penelitian ini bertujuan untuk menganalisis pengaruh kesadaran keamanan digital terhadap perilaku perlindungan data pribadi mahasiswa Universitas Methodist Indonesia. Penelitian ini menggunakan pendekatan kuantitatif dengan desain asosiatif kausal terhadap 102 responden yang dipilih melalui teknik convenience sampling. Data dikumpulkan menggunakan kuesioner dan dianalisis menggunakan regresi linear sederhana. Hasil penelitian menunjukkan bahwa kesadaran keamanan digital berpengaruh positif dan signifikan terhadap perilaku perlindungan data pribadi (B = 0,621; t = 9,876; p < 0,001), dengan kemampuan menjelaskan 49,4% variasi perilaku (R² = 0,494). Temuan ini menegaskan bahwa peningkatan kesadaran keamanan digital merupakan fondasi penting dalam membentuk perilaku perlindungan data pribadi serta memperkuat upaya pengembangan literasi keamanan siber di era masyarakat digital.